The Role of Microfinance on Women Empowerment. A Case Study of Segullah Microfinance, Kampala - Mercyline Adhiambo Otieno (Uganda Christian University, 2024)
The purpose of the study was to examine the role of microfinance on women empowerment. The research was driven by three distinctive objectives namely; to examine the role of microcredit on women empowerment, to examine the role of micro savings on women empowerment and to examine the role of micro leasing on women empowerment. The study used a cross sectional research design and focused on Segullah Microfinance, Kasubi. The study population was 110 and sample size was 86 who were determined using the Krejce and Morgan table. The respondents were chosen using simple random sampling and the study used both qualitative and quantitative research approaches for data collection. Interpretation of data was made to describe the research findings which revealed that microfinance actually plays a role in women empowerment. A big percentage of respondents agreed that access to microfinance products micro credit, micro savings and micro leasing improved their decision making, improved their social status, improved their financial literacy and also enhanced their social status. The study recommends that Microfinance should lower interest rates on micro credits to make it more accessible to women from low income backgrounds and also Microfinance institutions should partner with community based organisations and local leaders in communities to promote gender equality and women’s rights.
Undergraduate research